Estrutura da comunidade de macroinvertebrados bentônicos em um rio subtropical - Mangolin, Loana Priscila (2016)
Freshwater ecosystems are home to a wide variety of organizations and one of the animals groups that live in these ecosystems are the benthic macroinvertebrates. These animals are considered very important as they play a key role in energy transfer from the basal resources for the trophic levels more high food chains. Understanding how these groups are structured, their composition and diversity assists in the evaluation of the characteristics of the aquatic environment in which they live. Thus, to understand the taxa distribution patterns at different spatial and temporal scales, this study aimed to: I) Carry out a faunal survey in order to II) to verify the existence of spatial difference (between sampling points) and temporal (seasons) and III) possible relationships between some environmental factors with the distribution pattern of benthic macroinvertebrate community in an excerpt from a subtropical river (Rio São Francisco True) in the western region of Parana state. The study was conducted in a region near the city of Toledo during the period April 2013 to April 2014. The collections were fortnightly using artificial substrates also physico-chemical analysis of water were held, where the results were compared to standards Brazilian water quality pair freshwaters Class 2 (CONAMA n0 357/2005). The data were subjected to statistical analysis. On results there was a spatio-temporal variation in the composition and diversity of families of the benthic macroinvertebrate community where the smallest differences were found in point 6. The physico-chemical variables had influence in the distribution, diversity and composition of benthic macroinvertebrate community in which only point 6 met outside the standards allowed by CONAMA for Class 2. Based on the results, we can conclude that the analyzed stretch of the São Francisco True river is environmentally sound, except point 6 who suffers direct influence of the urban section of the city.